The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/pssa.200306470
|View full text |Cite
|
Sign up to set email alerts
|

Formation of porous layers on InSb(100) by anodization

Abstract: The present work deals with anodization processes of n-type InSb(100). Preferential etching of InSb can be electrochemically initiated in HCl, HBr and HF solutions. Except for etch features also the formation of porous layers can be observed. The resulting features were characterized by SEM and AES measurements. Due to the narrow bandgap of the material the results of the anodization process are neither sensitive to illumination of the n-type material nor to the doping level. The morphology of the attack depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…6, the counter anions X À in halogen acids (with X ¼ F, Br, Cl) play a crucial role determining the pore topography [38]. Note that a porous film exhibiting a different chemical composition than the substrate is formed onto InSb in HX [151] and onto InP in (NH 4 ) 2 S [152].…”
Section: Aqueous Electrolytesmentioning
confidence: 98%
“…6, the counter anions X À in halogen acids (with X ¼ F, Br, Cl) play a crucial role determining the pore topography [38]. Note that a porous film exhibiting a different chemical composition than the substrate is formed onto InSb in HX [151] and onto InP in (NH 4 ) 2 S [152].…”
Section: Aqueous Electrolytesmentioning
confidence: 98%
“…In both cases, it can be noted that a steep current increase takes place at a given voltage value (around 0.06 V for HF electrolyte, and 0.24 V for HCl electrolyte). In previous works on anodization of III-V semiconductors [6,15,16] similar I-V curves have been reported, and the voltage value corresponding to the fast current increase has been defined as the pore formation potential (PFP), i.e. the potential at which electrochemical dissolution of the material begins.…”
Section: Experimental Methodsmentioning
confidence: 82%
“…Unfortunately, these publications neither describe the morphology of the resulting layers, nor do they present SEM images. A porous structure of Sb-alloys obtained by anodic polarisation in the presence of halide acid solutions has been reported relatively rarely [58]. Schmucki et al have shown that upon anodising n-type InSb(100) in HCl solution, black porous layers of Sb 4 O 5 Cl 2 compound are obtained.…”
Section: Resultsmentioning
confidence: 99%